A Research and Critical Review of the Quarterly "Amlak" Mardan's Zafar Iqbal No - Ishaq, Muhammad; Khalil, Sadia; Saddique, (sourcecoder, 2023)
Zafar Iqbal, a pioneer of modern Ghazal, not only revitalized this poetic tradition but also liberated it from classical confines, infusing it with fresh innovation. His linguistic artistry and creative genius transformed the Ghazal's style and intellectual landscape. "Amlak," published from the outskirts of Mardan, released the "Zafar Iqbal Number," a noteworthy attempt at comprehending his style. The critical analyses within this publication offer multifaceted insights into Iqbal's poetry, addressing fundamental questions related to his Ghazals.